Defining appropriateness criteria for endoscopic sinus surgery in the management of adult dental implant patients with incidental maxillary sinus findings on conebeam computed tomography. (6th August 2020) - Amin, Nikul; Walker, Abigail; Alobid, Isam; Anari, Shahram; Bast, Florian; Bhalla, Rajiv K.; Cathcart, Russell; Harries, Philip G.; Hathorn, Iain; Philpott, Carl M.; Ramakrishnan, Yujay; Stew, Benjamin; et al.
Abstract: Objectives: Conebeam computed tomography (CBCT) imaging is commonly requested by dental implant surgeons, preoperatively, for patients being considered for dental implants. Incidental maxillary sinus findings often result in otolaryngology (ENT) referral for further assessment. CBCT findings include transient and benign mucosal changes that may not require any intervention and therefore unnecessarily delay implant surgery. We aim to define appropriateness criteria for ESS in the management of adult dental implant patients with incidental maxillary sinus findings on CBCT and provide guidance to both dental implant and ENT surgeons. Design: The RAND/UCLA appropriateness methodology was used to develop and define the appropriateness criteria. Setting: A virtual panel of 13 international experts in ESS. Participants: The expert panel completed two rounds of a modified Delphi ranking process for nine clinical scenarios, considering various factors affecting decision‐making processes. Main outcome measures: To define appropriateness criteria for ESS in adult dental implant patients who have incidental maxillary sinus findings on CBCT. Results: Patients with clinical symptoms and endoscopic findings of chronic rhinosinusitis together with an obstructed ostiomeatal complex (OMC) and concentric mucosal thickening of the ipsilateral maxillary sinus or pansinusitis were deemed appropriate candidates for ESS prior to their dental implant. ESS was not appropriate in asymptomatic patients with a patent OMC and mucosal thickening isolated to floor of the ipsilateral maxillary sinus. For uncertain scenarios, further discussion between dental implant and ENT surgeon should be considered. Conclusions: This study has developed and reported a list of appropriateness criteria to offer ESS in adult dental implant patients with incidental maxillary sinus findings on CBCT.